2016
DOI: 10.1371/journal.pone.0168157
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Characterization of Intact Cells Reveals Intracellular Amyloid Beta but Not Its Precursor Protein to Reduce Mitochondrial Respiration

Abstract: One hallmark of Alzheimer´s disease are senile plaques consisting of amyloid beta (Aβ), which derives from the processing of the amyloid precursor protein (APP). Mitochondrial dysfunction has been linked to the pathogenesis of Alzheimer´s disease and both Aβ and APP have been reported to affect mitochondrial function in isolated systems. However, in intact cells, considering a physiological localization of APP and Aβ, it is pending what triggers the mitochondrial defect. Thus, the aim of this study was to diss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 62 publications
1
25
1
Order By: Relevance
“…Mitochondrial beta-amyloid is correlated with mitochondrial dysfunction, including suppression of the mitochondrial membrane potential[79], and inhibition of respiratory complex I[80], complex IV[25], ABAD[24, 81], and SOD1[82]. Mitochondrially associated Aβ may be derived from extracellular pools of Aβ[31], or via cleavage of APP misdirected to mitochondria[83, 84] followed by direct internalization via the TOM complex[26]. On the other hand, evidence recently published by Cenini et al suggest that mitochondrially-associated Aβ is not internalized but is instead non-specifically bound to the mitochondrial outer membrane[30].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mitochondrial beta-amyloid is correlated with mitochondrial dysfunction, including suppression of the mitochondrial membrane potential[79], and inhibition of respiratory complex I[80], complex IV[25], ABAD[24, 81], and SOD1[82]. Mitochondrially associated Aβ may be derived from extracellular pools of Aβ[31], or via cleavage of APP misdirected to mitochondria[83, 84] followed by direct internalization via the TOM complex[26]. On the other hand, evidence recently published by Cenini et al suggest that mitochondrially-associated Aβ is not internalized but is instead non-specifically bound to the mitochondrial outer membrane[30].…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria possess approximately 1500 proteins, and nuclear genes encode greater than 95% of these, which are synthesized on cytosolic ribosomes, and are imported through the TOM ( T ranslocase of the O uter M embrane) apparatus; Tom40 is the central pore of this apparatus, the gateway for protein entrance into the mitochondrion (reviewed in[27]). Beta-amyloid peptides and mis-directed amyloid precursor protein interfere with mitochondrial protein import and disrupts mitochondrial function[2831]. These results suggest alterations in the function of the TOM apparatus and mitochondrial protein import contribute to Alzheimer’s disease pathology.…”
Section: Introductionmentioning
confidence: 99%
“…Our in vitro studies have sought to elucidate the effects of wild‐type APP and its non‐amyloidogenic fragments, particularly sAPPα, on mitochondrial function, seeking to distinguish the physiological role of APP and its non‐amyloidogenic fragments from the known toxic effects of excessive Aβ resulting from overexpression of mutant versions of APP. Overexpression of wild‐type APP reduces mitochondrial respiration in vitro , while higher levels of Aβ, either by overexpression of mutant APP harbouring the Swedish mutation (Lopez Sanchez et al, ), or via overexpression of BACE1 (Schaefer et al, ), do not alter mitochondrial respiration. We found that this reduction in respiratory capacity in neuronal cells overexpressing APP correlated with reduced transcription of mtDNA and a metabolic switch to glycolytic metabolism, suggesting a programmed down‐regulation of OXPHOS (Lopez Sanchez et al, ).…”
Section: App and Mitochondrial Metabolismmentioning
confidence: 99%
“…There is a cholesterol-dependent activity of gamma-secretase which links the interrelationship between a cholesterol-enriched lipid raft and amyloidogenic processing of APP. Future work may also determine BACE1 and gamma-secretase activities along with mitochondrial membrane potential (e.g., [40]), in order to display a better picture of the cytotoxicity event.…”
Section: Experiment-3: Variation Of β-Amentioning
confidence: 99%